Consumer Fruit Preferences: The Role of Nutrition Knowledge in Fruit Purchase and Consumption - Onyenweaku, Eridiong O. (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2022)
This study aims at ascertaining consumer fruit preferences and role of nutrition knowledge in consumers’ attitudes and practice as it concerns fruit consumption. An online questionnaire was used for this cross-sectional survey carried out in South Africa. The questionnaire link was circulated in the nine provinces for 4weeks; information gathered include sociodemographic data, respondents’ nutrition knowledge, and consumer fruit preferences alongside their fruit consumption patterns. Based on their responses, Nutrition Knowledge Scores (NKS) were calculated. Pearson correlation test was used to check for any relationship between the NKS, some sociodemographic factors and fruit preferences/consumption (significance was accepted at p<0.05). Three provinces; Gauteng, North West and KwaZulu-Natal accounted for over 70% of the 517 responses received. Almost half of the surveyed population had high NKS (45.5%) while 27.3% scored moderately and another 27.3% low. The most preferred fruits were oranges, bananas, and mangoes; others such as plums and berries were also preferred but not as consumed as the others due to their seasonal nature. The results show a positive relationship (p<0.001) between nutrition knowledge and fruit consumption frequency and healthy dietary patterns, but only significant but weak correlation between respondents’ nutrition knowledge and priority factors that affect their dietary product choices and purchases. Nutrition education is vital in enhancing awareness that will in turn yield positive results in fruit consumption and health outcomes.